A Study Of Transformational Change The Case Of Telekom Sales And Service Sdn.Bhd - Ahmad, Md. Nasir (2000)
The study was conducted through a questionnaire survey distributed to the employees of Telekom Sales and Services Sdn Bhd to all levels within the organisation. Visionary leadership and culture of the organisation was empirically tested for the relationship to the perceived success of transformational change efforts carried out by the organisation. It is hoped that the findings would be used as further inputs to achieve the desired effectiveness in the leadership and organisation culture change and the success of the transformational change program.